Natural Regeneration After Gold Mining in the Peruvian Amazon: Implications for Restoration of Tropical Forests - Chambi Legoas, Roger (2021)
Context: Gold mining is the most destructive activity in the natural forests of the Madre de Dios region in the southeastern Peruvian Amazon. Understanding the natural regeneration process of these degraded areas is necessary to develop forest restoration projects in such conditions. Aims: We aimed to evaluate forest recovery and identify the successional and structure patterns of vegetation governing natural regeneration over time. Methods: Structure, composition, richness, diversity, and successional status were evaluated in abandoned artisanal gold mine areas in Madre de Dios, southeastern Peru. Vegetation data were recorded in 61 plots of 250 m2 established in five sites varying from 1 to 19 years of abandonment. Vegetation in abandoned areas was compared with six undisturbed forests evaluated in previous inventories. Results: In the mining lands, tree density and basal area recovered quickly, while species richness and composition were slow. Forest recovery is an initial stage of transition from pioneer to early secondary species until at least 19 years after abandonment. The most abundant and frequent species were the fast-growing species Ochroma pyramidale and Cecropia engleriana. These species could be considered potential candidates to promote restoration plans. Pioneer species represented 63% of the number of species in plots of 1–4 years, 57% in plots of 5–7 years, and 50% in plots of 8–19 years. Early and late secondary species represented 34 and 16%, respectively, of the number of species in plots of 8–19 years. Abandoned mining and reference plots present less than 5% of species in common. Conclusion: Our results highlight a slow natural regeneration process in areas for up to 19 years after gold mining. Species from different successional statuses were identified as potential candidates for recovering vegetation in such areas. Our findings may have important implications for further research focusing on the ecological restoration in tropical forests severely degraded by gold mining.